Teaching from the thinking heart : the practice of holistic education - Miller, John P., 1943-; Irwin, Michelle; Nigh, Kelli (Emerald Publishing Limited : Information Age Publishing Inc., 2014)
This book includes papers written by teachers and how they engage holistic education in their classrooms. The papers come from a course taught by Jack Miller at the Ontario Institute for Studies in Education at the University of Toronto entitled The Holistic Curriculum. This is a rich and diverse collection of papers showing how holistic education can be brought into public education despite the pressures of testing and other accountability measures. Although most of the teachers teach in public schools there are also examples from teachers working in private and post secondary settings. This book can inspire other teachers who are looking for ways to teach the whole person in a more connected manner.There are very few texts in the field of holistic education that include the voices and practices of teachers, particularly those working in public schools. Many of the examples of holistic education in practice come from Waldorf, Montessori, Reggio Emilia and alternative schools. A unique feature of this book is the many different voices of teachers describing their work in the classroom; they talk about their successes, the challenges and even a few failures.